Participative Management: a Model of Islamic Perspective of Management (Shura) in an Organization (Global Journal of Management and Business Research, 2019)
Management is one of the core corners in our societal activities. (Patwary, 2003). It refers to a process of influencing and supporting others to work enthusiastically towards achieving objective (Koontz, 1994). It is a major factor for the success of any organization whether it is small or large, formal or informal. An effective management is a necessary for attaining success in business concern, government and political parties. Management is an approach of getting things done through other most effectively and efficiently in an organization. However on the Islamic perspective, employee are not completely sentient whether Islam is encouraging to engage in decision making and the consciousness in them to partake to the best of their ability towards improving output. In addition, there is problem of job satisfaction among staff as a result of non holistic participative management model in organization. This research tends to study the practice of participatory management model in particular emphasis on Islamic perspective, the extend of the participation in decision making by employees, the Islamic perspective on participative management and the impact of participatory management on efficiency and job satisfaction.